Performance Evaluation of Energy Collection Using Various Solar Flat Plate Collectors - Mohd Taupek, Muhammad Muhaimin; Awang, Mariah; Mohd Basir Ruddin, Nurhanis; Hamidon, Nuramidah; Ahmad, Faridahanim; Lukiyanto, Kukuh (Rsis, 2025)
Solar radiation, emitted by the sun and collected using solar collectors, can be converted into sound thermal energy. One of the most efficient energies harvesting methods is using solar Flat Plate Collectors (FPCs). These collectors’ function by heating water from atmospheric temperature, which can be used for domestic and industrial applications. This study evaluates the performance of different types of FPCs, including color variations (black vs. white collectors), material (copper vs. polypropylene collectors), and glazing (double vs. single glazing collectors), using the Energy Solar Trainer. The experiments were conducted over three days under clear sky conditions, with ambient temperatures ranging from 20°C to 36.2°C. Data were collected from 9:00 a.m. to 5:00 p.m., with a fixed solar radiation intensity of 722 W/m² and a flow rate of 2 L/min. The results indicate that black collectors outperform white collectors, copper collectors are more efficient than polypropylene collectors, and double-glazing collectors have higher efficiency than single glazing collectors. Overall, double-glazing collectors demonstrated the highest efficiency among the tested FPCs. These findings provide valuable insights into optimizing solar energy collection for enhanced thermal performance in various applications.